Preservice Teachers’ Readiness Towards Integrating AI-Based Tools in Education: A TPACK Approach - Angelina Bautista , Christine Estrada , Andrei Melvin Jaravata Laina Mae Mangaser , Ferdinand Narag , Rachell Soquila Raphael Job Asuncion (Educational Process: International Journal)
Background/Purpose – Technological pedagogical content knowledge (TPACK) emphasizes the effective integration of artificial intelligence (AI)-based tools in education, where specific knowledge is measured individually. This research determines the readiness of preservice teachers (PSTs) to integrate AI-based tools in education through the TPACK approach.